2015
DOI: 10.1007/s11071-015-2571-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of nonlinear system based on deep learning framework

Abstract: Abstract.A novel modeling based on deep learning framework which can exactly manifest the characteristics of nonlinear system is proposed in this paper. Specifically, a Deep Reconstruction are the simulated two-tone signal and actual square wave signal. The second system is a permanent magnet synchronous motor (PMSM) servo control system based on fuzzy PID control strategy. In terms of simulated and actual speed curves, BP-RBMs, DRM and ENN model are adopted on comparison respectively. It is shown by experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…These are much higher than the reasonable range of 6.0-7.0. Once housing prices decrease, local governments would face a serious debt crisis from declining land values, properties developed by real estate enterprises would be unsellable, individuals would bear enormous losses [47,48], and banks could not recover their loans, which might finally cause financial and even economic crisis. The outcome of developments in Japan in the 1980s is a valuable lesson.…”
Section: Discussionmentioning
confidence: 99%
“…These are much higher than the reasonable range of 6.0-7.0. Once housing prices decrease, local governments would face a serious debt crisis from declining land values, properties developed by real estate enterprises would be unsellable, individuals would bear enormous losses [47,48], and banks could not recover their loans, which might finally cause financial and even economic crisis. The outcome of developments in Japan in the 1980s is a valuable lesson.…”
Section: Discussionmentioning
confidence: 99%
“…The data of these communication styles is similar but not compatible because of the lack of unified interaction interfaces. (2) Due to the lack of service contents [80,81] and service styles, the information is transferred from the ship terminal to the coast station only to meet the requirement of the administration. A general service platform should be established to provide various information services.…”
Section: The Limit Of Transmission For the Waterway Traffic Informationmentioning
confidence: 99%
“…On the contrary, in the later stage of the search, c 1 takes a smaller value, while c 2 takes a larger value, which can make the particles learn more from the social optimal solutions and learn less from their own optimal solutions, and is conducive to quickly converge to the global optimal solution. In addition, in the reference literature [32][33][34], the relative nonlinear adjustment pairing experiments were carried out, and it was found that when the sum of c 1 and c 2 is less than 3, the algorithm performance is the best. Therefore, the learning factor of asynchronous change strategy is adopted in this study, as shown in Equations (9) and (10).…”
Section: Location Prediction Model Based On Pso-fnnmentioning
confidence: 99%